Branquitude, gênero e patriarcado na sociedade brasileira pela obra de Oliveira Paiva - Souza, Gabriela Ramos (2024)
This thesis analyzes the novels Afilhada ([1889] 1961) and Dona Guidinha do Poço ([1894] 1952), as well as the short stories O ódio (1887), Corda sensível (1887), and A paixão (1888) by the writer Oliveira Paiva (1861-1892). It highlights the need to update critical paradigms in literary analysis, since the works in question were produced at the end of the 19th century while the main critiques were published in the second half of the 20th century. Contemporary categories such as gender, race, and social class are used. The hypothesis is that the narrative voices express values of patriarchy and whiteness, as the literary text makes evident the sexism and racism of Brazilian society at that historical moment. Studies on whiteness are employed in the theoretical-methodological approach, and a canonical racist tradition in Brazilian literature is identified, which propagates the narcissistic pact of whiteness, silencing and degrading Black characters while exalting white ones. A gender lens reveals the expected role of white women in 19th-century society, both in the countryside and in urban spaces, as well as the influence of the bourgeois patriarchal family unit. The way in which intersectionality manifests in the presentation of female characters is also analyzed. Furthermore, the supposed adultery of the protagonist of Dona Guidinha do Poço, traditionally indicated by literary critics, is questioned by demonstrating the inconsistency of this alleged behavior in the narrative construction, which employs a multifaceted discourse. Finally, the sexualization of women and racism are proven by the omniscient narrative voice in both novels. Theoretical references include Coutinho (1996), Santiago (2000), and Süssekind (1984) on comparative literature and colonial heritage in literature; Pereira (1988) and Pinto (1967) to reflect on Oliveira Paiva's work; Cardoso (2022; 2020), Bento (2022), and Munanga (1999) on whiteness and race; Saffioti (2015) and Caulfield (2000) on gender issues; Akotirene (2019) and Collins; Bilge (2021) on intersectionality.